Some economics of global warming - Schelling, Thomas C. (American Economic Review, 1992)
The greenhouse effect itself is simple enough to understand and is not in any real dispute. What is in dispute is its magnitude over the coming century, its translation into changes in climates around the globe, and the impacts of those climate changes on human welfare and the natural environment. These are beyond the professional understanding of any single person. The sciences involved are too numerous and diverse. Demography, economics, biology, and the technology sciences are needed to project emissions; atmospheric chemistry, oceanography, biology, and meteorology are needed to translate emissions into climates; biology, agronomy, health sciences, economics, sociology, and glaciology are needed to identify and assess impacts on human societies and natural ecosystems. And those are not all. There are expert judgments on large pieces of the subject, but no single person clothed in this panoply of disciplines has shown up or is likely to. This article makes an attempt to forecast the economic and social consequences of global warming due to anthropogenic greenhouse gases, and attempting to prevent it.